Novel and conserved drought-responsive microRNAs expression analysis in root tissues of wheat (Triticum asetivum L.) at reproductive stage - Sharma, Pradeep; Mishra, Shefali; Kaur, Amandeep; Ahlawat, O. P.; Tiwari, Ratan (Frontiers in Plant Science, 2025)
IntroductionMicroRNAs (miRNAs) are a class of 20- to 24-nucleotide endogenous small RNAs that regulate gene expression post-transcriptionally, playing vital roles in plant development and stress responses. Among abiotic stresses, drought stress (DS) is one of the most critical factors affecting wheat yield worldwide. Understanding miRNA-mediated regulatory mechanisms under drought stress conditions is crucial for improving drought tolerance in wheat.MethodsTo identify drought-responsive miRNAs in wheat, small RNA libraries were constructed from drought-tolerant (NI5439) and drought-susceptible (WL711) genotypes subjected to both control and drought-stress conditions. High-throughput sequencing was used to identify known and novel miRNAs. The family distribution of miRNAs, target prediction, pathway analysis, and differential expression analysis were conducted. A heat map was generated for the top 50 up- and downregulated miRNAs, and novel miRNAs were validated through qRT-PCR.Results and discussionA total of 306 known and 58 novel miRNAs were identified across the two wheat genotypes. The identified miRNAs belonged to over 18 families, with miR9662a-3p being the most abundant. Most identified miRNAs were 21 nucleotides in length. A total of 2,300 target genes were predicted for the known miRNAs. Pathway analysis revealed that target genes were involved in key biological processes including signal transduction, transport, organelle localization, DNA methylation, histone and chromatin modification, and plant development. Ten novel miRNAs were validated using qRT-PCR, confirming their differential expression under drought stress. The findings significantly expand the repertoire of drought-responsive and novel miRNAs in wheat. These miRNAs and their target genes provide valuable insights into the molecular mechanisms underlying drought tolerance. The validated novel miRNAs represent potential targets for genetic manipulation to enhance drought resilience in wheat cultivars.ConclusionThis study provides a comprehensive miRNA expression profile in wheat under drought conditions and highlights several novel miRNAs that are differentially expressed between tolerant and susceptible genotypes. The integration of sequencing, computational analysis, and qRT-PCR validation strengthens the utility of these findings for future functional genomics studies and breeding programs aimed at developing drought-tolerant wheat varieties.